1986
DOI: 10.1111/j.1399-3011.1986.tb01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient method for the preparation of Fmoc‐amino acids starting from 9‐fluorenylmethanol

Abstract: A method is presented for the high‐yield synthesis of Fmoc amino acids, which precludes racemization and over‐reaction due to carboxyl activation. A detailed procedure is given for the preparation of Fmoc‐ONSu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 8 publications
2
40
0
1
Order By: Relevance
“…Commercial L-alanine, deuterated at C ␣ and C ␤ carbons (Ala-d 4 ), from Cambridge Isotope Laboratories (Andover, MA) was derivatized with an Fmoc-protecting group as described previously (21,22). DLPC, DMPC, and DOPC were purchased from Avanti Polar Lipids (Alabaster, AL).…”
Section: Methodsmentioning
confidence: 99%
“…Commercial L-alanine, deuterated at C ␣ and C ␤ carbons (Ala-d 4 ), from Cambridge Isotope Laboratories (Andover, MA) was derivatized with an Fmoc-protecting group as described previously (21,22). DLPC, DMPC, and DOPC were purchased from Avanti Polar Lipids (Alabaster, AL).…”
Section: Methodsmentioning
confidence: 99%
“…9,10 The introduction of the alkoxycarbonyl moiety was first carried out under weakly basic conditions via the Schotten-Baumann reaction, by using the corresponding chloroformates (also known as chlorides). 3 However, our group 11 and others [12][13][14][15] described in the early eighties that during the preparation of Fmocamino acids from Fmoc-Cl, most amino acids become contaminated with significant levels (1-20%) of corresponding Fmoc-dipeptides and even tripeptides. As an example, even when the relatively hindered Alloc-Val-OH was prepared in a laboratory scale, 14% of the corresponding dipeptide was obtained.…”
mentioning
confidence: 96%
“…[11] Nevertheless, it has been reported that the high reactivity of these chlorides, such as Fmoc-Cl (1) or Alloc-Cl (2), might lead to the formation of amino-acid-based byproducts, including the protection of bulky residues, that become inserted into the peptide chain. [12][13][14][15][16] As result of this detrimental side reaction, considerable formation of Fmoc/Alloc-dipeptides and tripeptides (1-20 %) has been observed, as established by HPLC, amino acid analysis, NMR spectroscopy, and the synthesis of a number of standards. [13] A previous "in situ" bis-trimethylsilylation step of protection of the residue, before conducting the reaction with the chloroformate, can prevent the formation of such byproducts.…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15][16]26,27] Nonetheless, the formation of up to 0.4 % of some amino-acid-based byproducts like Fmoc/Alloc-β-Ala-OH and Fmoc/Alloc-β-Ala-AA-OH can occur when using this reagent for α-amino protection. [28] A detailed discussion of the mechanism of this side reaction has been proposed by Isidro-Llobet et al [25] Azide derivatives, which can be used as solids after isolation from the chloroformates [12,29] or formed in situ before reacting with the amino acid, [30] have also been proposed as an alternative pathway to the N-protection of amino acids, although its explosive nature compromises its use in large-scale synthesis.…”
Section: Introductionmentioning
confidence: 99%